Enhancing bone tissue engineering with 3D-Printed polycaprolactone scaffolds integrated with tragacanth gum/bioactive glass - Janmohammadi, Mahsa; Nourbakhsh, Mohammad Sadegh; Bahraminasab, Marjan; Tayebi, Lobat (Materials today bio, 2023)
Tissue-engineered bone substitutes, characterized by favorable physicochemical, mechanical, and biological properties, present a promising alternative for addressing bone defects. In this study, we employed an innovative 3D host-guest scaffold model, where the host component served as a mechanical support, while the guest component facilitated osteogenic effects. More specifically, we fabricated a triangular porous polycaprolactone framework (host) using advanced 3D printing techniques, and subsequently filled the framework's pores with tragacanth gum-45S5 bioactive glass as the guest component. Comprehensive assessments were conducted to evaluate the physical, mechanical, and biological properties of the designed scaffolds. Remarkably, successful integration of the guest component within the framework was achieved, resulting in enhanced bioactivity and increased strength. Our findings demonstrated that the scaffolds exhibited ion release (Si, Ca, and P), surface apatite formation, and biodegradation. Additionally, in vitro cell culture assays revealed that the scaffolds demonstrated significant improvements in cell viability, proliferation, and attachment. Significantly, the multi-compartment scaffolds exhibited remarkable osteogenic properties, indicated by a substantial increase in the expression of osteopontin, osteocalcin, and matrix deposition. Based on our results, the framework provided robust mechanical support during the new bone formation process, while the guest component matrix created a conducive micro-environment for cellular adhesion, osteogenic functionality, and matrix production. These multi-compartment scaffolds hold great potential as a viable alternative to autografts and offer promising clinical applications for bone defect repair in the future. [Display omitted] •Polycaprolactone framework as a host component was designed via 3D printing.•Tragacanth gum- 45S5 bioactive glass as a guest component was integrated with the framework.•The release of ions from the host-guest scaffolds improved the bioactivity response.•Guest component enhanced the stiffness of the host component.•Host-guest scaffolds induced cell viability, differentiation, and protein expression.